2022
DOI: 10.1002/clc.23776
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponins predict mortality and cardiovascular outcomes in patients with peripheral artery disease: A systematic review and meta‐analysis of adjusted observational studies

Abstract: Background A significant proportion of patients (pts) with peripheral artery disease (PAD) have concomitant coronary artery disease and polyvascular involvement contributes to increased risk of death and unfavorable cardiovascular events. Hypothesis Cardiac troponins are associated with adverse cardiovascular outcomes in PAD pts. Methods We systematically searched Medline and Scopus to identify all observational cohort studies published before June 2021 (combining terms “troponin,” “peripheral artery disease,”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Cox regression was used to investigate unadjusted and adjusted significant associations between positive troponin concentrations and primary and secondary outcomes, which were expressed as hazard ratios with 95% confidence intervals (95% CI). To adjust models, we used age and sex and other known confounding factors for troponin elevation according to the literature (diabetes, hypertension, previous ischemic heart disease, previous peripheral vascular disease and renal failure -measured through estimated glomerular filtration rate) [12,13] if they were differently distributed between the two groups (patients with positive and negative troponin values) in the univariate analysis. In addition, interaction by sex was measured in all outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cox regression was used to investigate unadjusted and adjusted significant associations between positive troponin concentrations and primary and secondary outcomes, which were expressed as hazard ratios with 95% confidence intervals (95% CI). To adjust models, we used age and sex and other known confounding factors for troponin elevation according to the literature (diabetes, hypertension, previous ischemic heart disease, previous peripheral vascular disease and renal failure -measured through estimated glomerular filtration rate) [12,13] if they were differently distributed between the two groups (patients with positive and negative troponin values) in the univariate analysis. In addition, interaction by sex was measured in all outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this study, elevated troponin concentration was observed in 5.3% (range: 4.4%–8.7%) of patients with intermittent claudication and in 62.6% (range: 33.6%–85%) of patients with CLTI. An elevated troponin level was significantly associated with an increased risk of all-cause mortality (HR: 2.85, 95% CI: 2.28–3.57) and risk of major adverse cardiovascular events (HR: 2.58, 95% CI: 2.04–3.26) [ 101 ].…”
Section: Cardiac Troponin Serum Level In Chronic Cardiovascular Diseasesmentioning
confidence: 99%
“…Individuals diagnosed with PAD not only face limb-related problems but also have an increased risk of cardiovascular events, including myocardial infarction (MI), stroke, and cardiovascular-related mortality. 1,4,5 In recent years, there has been a paradigm shift in the treatment of hypertension, with an emphasis on intensive blood pressure (BP) control. Clinical trials have shown that aggressive reduction of BP in certain populations can significantly reduce the risk of cardiovascular events, including MI, stroke, and heart failure (HF).…”
mentioning
confidence: 99%